The Ethnoecology of Sasak people in Mandalika, Lombok Island: Local Knowledge and Wisdom in Relation with Land Use - Rahayu, M.; Keim, A. P.; Nikmatullah, M.; Rustiami, H.; Susan, D.; Sujarwo, W. (Jurnal Pendidikan IPA Indonesia, 2021)
This current study is an ethnoecological study on land use for plant diversity by the Sasak people in Mandalika, Lombok Island, West Nusa Tenggara. Interview and direct observation methods were implemented. The study areas included the villages of Kuta, Mertak, and Sengkol. The results indicated four main groups of land: Leleah (a yard or home garden), bangket (rice fields, including the bangket gora; rice fields nurtured by rainfalls), kebon (gardens, including kebon kayo or garden of woody plants and kebon elalo or garden of crops), and gawah (forests, including gawah mali or sacred forests). This study results showed that despite the stress of a constantly changing environment and various restrictions and limitations, the ethnoecological knowledge in local wisdom is still maintained well.